Modeling the global bomb tritium transient signal with the AGCM LMDZ‐iso: A method to evaluate aspects of the hydrological cycle. Issue 21 (5th November 2016) - Cauquoin, A.; Jean‐Baptiste, P.; Risi, C.; Fourré, É.; Landais, A.
Abstract: Improving the representation of the hydrological cycle in atmospheric general circulation models (AGCMs) is one of the main challenges in modeling the Earth's climate system. One way to evaluate model performance is to simulate the transport of water isotopes. Among those available, tritium is an extremely valuable tracer, because its content in the different reservoirs involved in the water cycle (stratosphere, troposphere, and ocean) varies by order of magnitude. Previous work incorporated natural tritium into Laboratoire de Météorologie Dynamique Zoom (LMDZ)‐iso, a version of the LMDZ general circulation model enhanced by water isotope diagnostics. Here for the first time, the anthropogenic tritium injected by each of the atmospheric nuclear bomb tests between 1945 and 1980 has been first estimated and further implemented in the model; it creates an opportunity to evaluate certain aspects of LDMZ over several decades by following the bomb tritium transient signal through the hydrological cycle. Simulations of tritium in water vapor and precipitation for the period 1950–2008, with both natural and anthropogenic components, are presented in this study. LMDZ‐iso satisfactorily reproduces the general shape of the temporal evolution of tritium. However, LMDZ‐iso simulates too high a bomb tritium peak followed by too strong a decrease of tritium in precipitation. The too diffusive vertical advection in AGCMs crucially affects the residence time of tritium in the stratosphere. This insight into model performance demonstrates that the implementation of tritium in an AGCM provides a new and valuable test of the modeled atmospheric transport, complementing water stable isotope modeling. Key Points: The anthropogenic tritium injected by each of the atmospheric nuclear tests has been estimated and implemented in the AGCM LMDZ‐iso LMDZ‐iso correctly reproduces the general shape of the temporal evolution of tritium in precipitation between 1950 and 2008 Tritium model‐data comparisons provide an additional tool to test the stratospheric residence time in the models